Isometric shoulder and hip strength impact on throwing velocity and reactive strength - Kayhan, R. F.; Terzi, E.; Bayrakdaroglu, S.; Ceylan, H. I.; Biyikli, T. (International Journal of Sports Medicine, 2024)
The aim of the study is to examine relationships between shoulder extension-flexion and internal-external rotation strength of professional male handball players with throwing velocity, and the hip extension-flexion strength with horizontal and vertical reactive strength index. Fifteen professional male handball players participating in 1st League matches took part in the study. The results showed that isometric shoulder flexion and extension strength significantly predicted stable throwing velocity (r2=between 0.27-0.73) and dynamic throwing velocity (r2=between 0.30-0.62). In addition, isometric internal and external rotation strength significantly predicted stable throwing velocity (r2=between 0.32-0.54) and dynamic throwing velocity (r2=between 0.31-0.44). Moreover, isometric hip extension and flexion strength significantly predicted vertical reactive strength index (r2=between 0.31-0.45) and horizontal reactive strength index (r2=between 0.26-0.42). In conclusion, it was observed that shoulder strength has an enhancing effect on handball players' throwing velocity, while hip strength is a determining factor for the reactive strength index. In this context, it is assumed that shoulder weakness during throwing will affect the accuracy and velocity of throwing by disrupting the angular momentum, while weakness in the hip during the jump phase of the throwing motion will negatively affect the explosive power by limiting stabilization during landing.